Maladaptation: when adaptation to climate change goes very wrong - Schipper, ELF (Cell Press, 2020)
Adapting to climate change is necessary to ensure that the impacts will not overwhelm societies and ecosystems around the world. But planning adaptation is an exercise in uncertainty, and built on imperfect information, many adaptation strategies fail. Some go even further, creating conditions that actually worsen the situation; this is called maladaptation. Aside from wasting time and money, maladaptation is a process through which people become even more vulnerable to climate change. Poor planning is the primary cause of maladaptation, yet the diverse manifestations are complex, and identifying maladaptation in advance with certainty is difficult. Nevertheless, there is now sufficient experience to give an indication of how maladaptation can take place, the contexts that may be more prone to such an outcome, and the design flaws in strategies that need to be avoided. Until adaptation projects directly address the drivers of vulnerability, however, maladaptation will continue to be a risk.